Review of the catalogues in positional astronomy made in Mykolaiv - Pozhalova, Zh.A.; Petrov, G.M. (Кинематика и физика небесных тел, 2005)
More than 30 different catalogues of positional astronomy have been compiled at the Nikolaev Observatory since its foundation to present. Among them there are 11 absolute catalogues, 18 catalogues compiled by differential method, 5 special star zones of photographic observations of stars (archive of astroplates), and several thousands position determinations for Solar System bodies with different instruments.